PENGARUH PERHATIAN ORANG TUA DAN PERSEPSI ATAS KOMPETENSI GURU TERHADAP PRESTASI BELAJAR SOSIOLOGI (Survey Pada Siswa SMAN Di Kota Tangerang) - Ike Hilatun Nisa (STAI Asy-Syukriyyah, 2020)
Abstract This study is a survey and aims to find and analyze empirically the influence of parental attention on Sociology learning achievement, perceptions of teacher competence on Sociology learning achievement, the influence of parental attention and jointly on Sociology learning achievement. The research method used was a survey. Affordable population in this study were students of class XI in 4 public high schools in Tangerang City with a sample of 85 students. The research sample was obtained through a simple random sampling method in which the researcher mixed subjects in the population so that all subjects were considered equal. Data collection using instruments: questionnaires, and the collection of students' report cards Sociology. The collected data is then analyzed using correlation and multiple regression techniques. Before the data is analyzed, a descriptive statistical analysis and a data requirements test (normality test and linearity test) are conducted before the regression test is performed. This research was conducted in March 2016 to June 2016. The results showed that: 1) There was a significant influence of parents' attention (X1) and perceptions of teacher competence (X2) on sociology learning achievement (Y), this was evidenced by the value sig. 0,000 <0.05 and Fcount = 28,123. 2) There is a significant influence of parents' attention (X1) on the learning achievements of Sociology (Y), this is evidenced by the value of sig. 0,000 <0.05 and tcount = 5.210. 3) There is a significant influence of perception on teacher competence (X2) on the learning achievement of Sociology (Y), this is evidenced by the sig.0,000 value <0.05 and tcount = 5,400. The resulting regression equation is Y = 29,935 + 0,191X1 + 0,274X2.